A molecular phylogeny of nuclear and mitochondrial sequences in Hymenolepis nana (Cestoda) supports the existence of a cryptic species - MacNish, M.G.; Morgan-Ryan, U.M.; Monis, P.T.; Behnke, J.M.; Thompson, R.C.A. (Cambridge University Press, 2002)
Since isolates of Hymenolepis nana infecting humans and rodents are morphologically indistinguishable, the only way they can be reliably identified is by comparing the parasite in each host using molecular tools. In the current study, isolates of H. nana from rodent and human hosts from a broad geographical range were sequenced at the ribosomal first internal transcribed spacer (ITS1), the mitochondrial cytochrome c oxidase subunit 1 (C01) gene and the nuclear paramyosin gene loci. Twenty-three isolates of H. nana were sequenced at the ITS1 locus and this confirmed the existence of spacers which, although similar in length (approximately 646 bp), differed in their primary sequences which led to the separation of the isolates into 2 clusters when analysed phylogenetically. This sequence variation was not, however, related to the host of origin of the isolate, thus was not a marker of genetic distinction between H. nana from rodents and humans.Sequencing of a 444 bp fragment of the mitochondrial cytochrome c oxidase 1 gene (C01) in 9 isolates of H. nana from rodents and 6 from humans identified a phylogenetically supported genetic divergence of approximately 5% betweensome mouse and human isolates. This suggests that H. nana is a species complex, or ‘cryptic ’ species (=morphologically identical yet genetically distinct). A small segment of the nuclear gene, paramyosin, (625 bp or 840 bp) was sequenced in 4 mouse and 3 human isolates of H. nana. However, this gene did not provide the level of heterogeneity required to distinguish between isolates from rodent and human hosts. From the results obtained from faster evolving genes, and the epidemiological evidence, we believe that the life-cycle of H. nana that exists in the north-west of Western Australia is likely to involve mainly ‘human to human’ transmission.